HARNESSING ARTIFICIAL INTELLIGENCE IN ENGLISH AND UZBEK LANGUAGE TEACHING IN THE ERA OF DIGITAL TRANSFORMATION. - Khujaev Dilshod Gayratovich (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
As digitalization reshapes education worldwide, artificial intelligence (AI) is increasingly influencing how languages are taught and acquired. This article examines the integration of AI in teaching both English and Uzbek, highlighting how emerging technologies are enhancing instructional effectiveness, learner engagement, and accessibility. While English benefits from decades of technological integration, Uzbek is gradually embracing AI-driven language tools. By analyzing current trends, linguistic challenges, and the role of computational linguistics, this paper underscores the significance of AI in modern bilingual language instruction.